Reimagining the Jews of Ireland: historiography, identity and representation - Rodgers, Zuleika; Wynn, Natalie (Reimagining Ireland, 2023)
"This collection marks the coming of age of Irish Jewish Studies. Beautifully curated by Zuleika Rodgers and Natalie Wynn, it brings together the best of recent scholarship, covering history, politics, literature and everyday life. Taken together these essays show the complexity of both the Irish Jewish experience and responses to them." (Tony Kushner, James Parkes Professor of Jewish/non-Jewish relations, University of Southampton) "A refreshingly nuanced exploration of perceptions and self-perceptions of Irish Jews. The authors interrogate political, religious, economic, social and cultural discourses from the eighteenth century to contemporary times to unravel less-familiar expressions of antisemitism, alongside occasional philosemitism, and offer critical insights on the many reimaginations of Christian Ireland's long-standing migrant Other minority." (Guy Beiner, Sullivan Chair of Irish Studies, Boston College) Discourse, both scholarly and popular, around the Jews of Ireland has increased in recent years and this volume of essays takes up the challenge of placing it within the framework of Jewish historiography and the study of Jewish history and culture. The focus of the volume is to provide a critical re-evaluation of the study of Irish Jews looking at key areas such as Irish Jewish historiography, communal traditions, antisemitism, nationalism (Jewish and Irish) and representations in popular media. Underlying the contributions is the desire to reassess the ways in which traditional scholarship and representation of Irish Jews have been shaped by uninterrogated narratives and a lack of understanding and sensitivity to the context of Jewish history and the Jewish experience